APLIKASI BEBERAPA DOSIS LIMBAH CAIR TAHU BERBAHAN AKTIF Bacillus sp TERHADAP PERTUMBUHAN TANAMAN SAWI HIJAU (Brasicca rapa parachinensis L) - Betari ' Kartika; Fifi ' Puspita; Sri ' Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Mustard ( Brasica few parachinensis L ) is a popular and widely grown in Indonesia . To increase the production of mustard , it is necessary to fertilization. Fertilization is one of the important factors in the success of the cultivation of plant. One of the alternatives that can be used to reduce inorganic fertilizer is to use biological fertilizers. The purpose of this research is to determine the effect of various dosis of biological fertilizers which contain active ingredient Bacillus sp. and to get the best doses for the growth of mustard (Brasicca rapa parachinensis L). This research was conducted in the experimental field of Agriculture Faculty, University of Riau in April to Mei 2016. The study was conducted by using completely randomized design (CRD) consisting of 5 treatments and 4 replications. Data were analyzed statistically using analysis of variance (ANOVA) and followed by Duncan's New Multiple Range Test (DNMRT) at 5% level. Parameters measured were the plant height , leaf number , fresh weight of plants / plot , leaf area , root volume, weight of plants/plots in consumption. The results were analyzed statistically using analysis of varian Provision fertilizer active ingredient Bacillus sp. showed different results with the measurement of weight of the plant is consumed and broad leaf plants. The result showed that aren’t significantly different at parameter plant height, number of leaves and root volume. Provision of biological fertilizer active ingredient Bacillus sp. with doses 40 ml/polybag is the best dose for weight parameters consumed plant and leaf area. Keyword: Tofu liquid waste, Bacillus sp, Brasicca rapa parachinensis L